Badangan Sanak in the Syair Nasihat of Sultan Haji Omar 'Ali Saifuddien Sa'adul Khairi Waddien, the 28th Sultan of Negara Brunei Darussalam: (Badangan Sanak dalam Syair Nasihat Nukilan Sultan Haji Omar 'Ali Saifuddien Sa'adul Khairi Waddien, Sultan Negara Brunei Darussalam Ke-28) (Jurnal Bahasa, 2017)
Badangan sanak is a system of forms of address among Malay families under the Malay-Islamic monarchical system of Brunei Darussalam. This study is concerned with identifying the extent to which the forms of address play a role in strengthening familial ties within the Muslim Malay community of Brunei. The badangan sanak system has some relation to the preservation of family reputation in the extended family. The lexical items analysed and examined in this study are forms of address from the badangan sanak system as extracted from the Syair Nasihat written by Muda Omar 'Ali Saifuddien, the 28th Sultan of Brunei. This study reveals the familial attitudes promoted by the monarchy and how these have left an imprint in the lives of commoners. This system ensures continued  strong family ties and societal bonds that lie at the heart of the Malay-Islamic monarchical system.Keywords: Forms of address, badangan sanak, Syair Nasihat, Malay-Islamic Monarchy